Dilution reveals how viral lysis and grazing shape microbial communities. (8th February 2016) - Cram, Jacob A.; Parada, Alma E.; Fuhrman, Jed A.
Abstract: Grazing by protists and viral infection are the main known sources of marine bacterial mortality, and both processes shape the structure and ecology of microbial communities. We diluted planktonic microbial communities to determine how decreasing the encounter rate between bacteria, grazers, and viruses affects community structure. In experimental treatments, sea water was diluted 10‐fold in water from which protists and bacteria had been removed (0.2 μ m filtered), or from which protists bacteria and viruses had been removed (0.02 μ m filtered). In both dilution treatments, bacterial and protistan communities generally recovered within 3 d to near their original abundances, but viruses did not. The microbial community structure of bacteria in both diluted treatments was significantly different from untreated control communities, after 3 d, and significantly different between the 0.2 μ m and 0.02 μ m dilution treatments after 6 d. Diluted treatments were dominated by operational taxonomic units that are normally rare in near‐surface seawater, including some normally more abundant in the deep water at this location such as SAR324 and SAR406, while abundant surface taxa including SAR11 did not increase in abundance after dilution. These results are consistent with the hypothesis that microbes face a tradeoff between fast growth and resistance to predation and infection, and that microbes that are normally most abundant in the California coastal surface waters (such as SAR11 and Actinobacteria) are both more grazer resistant and slower growing than potentially opportunistic organisms that are rare in surface water but capable of fast net growth when grazers or viruses are removed.